Toksisitas Ekstrak Daun mangrove Rhizophora stylosa dari Pulau Maspari Sumatera Selatan - Muhtadi, Muhtadi; Ulqodry, Tengku Zia; Rozirwan, Rozirwan; Sarno, Sarno; Aryawati, Riris (Universitas Bangka Belitung, 2025)
The leaves of R. stylosa are a potential source of bioactive compounds for health and pharmacology. The composition of bioactive compounds in the leaves can be influenced by the ecological conditions and geographical location of this small island. This study aims to evaluate the toxicity and composition of bioactive compounds that are toxic in mangrove leaf extracts of R. stylosa from Maspari Island in coastal South Sumatra. A total of 1 kg of R. stylosa leaf samples were taken from Maspari Island then washed thoroughly to remove dirt, cut into small pieces, and dried in the sun using the indirect sunlight method covered with black cloth. The dried leaf samples were then pulverized into powder, and as much as 100 grams of fine powder was macerated with 96% ethanol solvent in a ratio of 1:10 (b/v). The maceration process was carried out for 1 x 24 hours, then the maceration solution was filtered and evaporated using a rotary evaporator at 60°C to become a concentrated extract. Toxicity tests were carried out using the Brine Shrimp Lethality Test (BSLT) method, while the identification of toxic bioactive compounds was carried out through phytochemical tests, total phenol tests, and GC-MS analysis. The test results showed that the LC50 value of R. stylosa leaf extract was 393 mg/mL (moderately toxic). The total phenol content was 442.82 (gGA/g), and the bioactive compounds identified included alkaloids, flavonoids, saponins, terpenoids, and acids such as Hexadecanoic acid, methyl ester, and trans-13-Octadecenoic acid, methyl ester.